Corporate rebranding on SMES: an analysis based on a framework appllied to big companies the case of Greenwish - Travassos, André Marques (2019)
The subject of corporate rebranding has been increasingly gathering consideration among several businesses and organizations, as they continuously attempt to create new and differentiated images in customers minds and/or adapt to the market characteristics. Numerous researches have been done on this theme. However, these studies have been made in large companies' context, regardless the fact of small and medium enterprises representing the most common type of businesses. Accordingly, SMEs differ a lot from large companies, therefore, it is necessary to study how the corporate rebranding process is carried in their context and environment. Bearing in mind the limited studies on corporate rebranding in SMEs, this case study is focused on the rebranding that Greenwish, a healthy food restaurant, has been through. By doing so, this case seeks to comprehend what were the main reasons and motivations to rebrand, and in which ways differed from big companies. Likewise, a deep analysis to the rebranding process itself is conducted, considering the subprocesses, stages and actors involved with the aim of comparing with a theoretical framework applied, again, on big corporations. Ultimately, the findings showed that the corporate rebranding process includes few actors and is mostly owner- driven, as all the actions and decisions revolved around her. Moreover, the findings present unsuitability of the company name as a novel reason for rebranding. Also, due to the nature of the company, corporate rebranding involved product rebranding as well, and (re)launching was almost non-existing. Similarly, many phases and subprocesses were intertwined and/or overlapped.